META-ANALYSIS OF PROJECT BASED LEARNING EFFECTS ON STUDENTS’ CREATIVE THINKING IN PHYSICS LEARNING - Novi Ramayani; Sri Purwaningsih; Pinta Murni; Ilham Falani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Developing creative thinking skills has become essential in the Fourth Industrial Revolution era. However, conventional teacher-centered instructional approaches have been found to be less effective in cultivating these abilities, particularly in complex subjects such as physics. Project-Based Learning (PjBL) has emerged as an instructional model with the potential to enhance students’ creative thinking in physics classrooms. This study investigates the influence of PjBL on various dimensions of students’ creative thinking skills in physics learning by synthesizing evidence from previous research. A meta-analysis approach was employed, with empirical data collected from Google Scholar using Harzing’s Publish or Perish 8 and organized through Mendeley reference management software. The search identified 28 studies published between 2014 and 2023, of which 13 met the inclusion criteria and provided adequate statistical data for effect size calculation. The analysis produced an effect size of 1.03, classified as high, indicating that PjBL contributes approximately 84% effectiveness in improving creative thinking skills. Furthermore, 19 of the included studies examined specific creativity indicators, showing that elaboration demonstrated the greatest improvement, while flexibility showed the lowest gains. Overall, the findings confirm that PjBL has a substantial positive impact on students’ creative thinking in physics education.